2017
DOI: 10.1080/03602532.2017.1293683
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease (NAFLD) – pathogenesis, classification, and effect on drug metabolizing enzymes and transporters

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a spectrum of liver disorders. It is defined by the presence of steatosis in more than 5 % of hepatocytes with little or no alcohol consumption. Insulin resistance, the metabolic syndrome or type 2 diabetes and genetic variants of PNPLA3 or TM6SF2 seem to play a role in the pathogenesis of NAFLD. The pathological progression of NAFLD follows tentatively a ‘three-hit’ process namely steatosis, lipotoxicity and inflammation. The presence of steatosis, oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
382
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(403 citation statements)
references
References 170 publications
(207 reference statements)
8
382
1
12
Order By: Relevance
“…NAFLD is the most common cause of chronic liver disease among children and adults all over the world [93][94][95], which is characterized by steatosis, ballooning degeneration, and fatty retention of liver parenchyma cells with no history of excessive alcohol intake or other known liver disease [96]. The pathological character of NAFLD is caused by metabolic dysregulation of de novo lipogenesis, fatty acid uptake, fatty acid oxidation, and triglycerides export [97,98]. Previous studies have found that m 6 A alteration is highly related to the development of NAFLD [34,99,100].…”
Section: A Methylation and Nafldmentioning
confidence: 99%
“…NAFLD is the most common cause of chronic liver disease among children and adults all over the world [93][94][95], which is characterized by steatosis, ballooning degeneration, and fatty retention of liver parenchyma cells with no history of excessive alcohol intake or other known liver disease [96]. The pathological character of NAFLD is caused by metabolic dysregulation of de novo lipogenesis, fatty acid uptake, fatty acid oxidation, and triglycerides export [97,98]. Previous studies have found that m 6 A alteration is highly related to the development of NAFLD [34,99,100].…”
Section: A Methylation and Nafldmentioning
confidence: 99%
“…Dysregulated immune responsiveness is central to the development and progression of NAFLD (9,10). In obesity, both liver resident (e.g., Kupffer cells, [KC], hepatic stellate cells, [HSC], hepatocytes) and infiltrating immune cells (e.g., neutrophils, dendritic cells [DC], natural killer [NK] cells, NKT cells, blood monocytes, T cells, B cells, and macrophages) contribute to NAFLD development and progression via systemic and tissue inflammatory mediator production (e.g., interleukin [IL]-17A, IL-6, tumor necrosis factor [TNF], IL-1β) (5,11).…”
Section: Immune Responses In Nafldmentioning
confidence: 99%
“…Thus, it is not surprising that several pharmacological drugs that target metabolic and inflammatory and molecular mechanisms important in NAFLD progression are currently being examined (188). Hepatic lipid accumulation is an initial driver of NAFLD pathogenesis (9,84). Intuitively, use of therapeutic drugs that target lipid metabolism is actively pursued.…”
Section: Therapiesmentioning
confidence: 99%
“…Similarly, we also confirmed that AG could prevent hepatosteatosis induced by the HFD through decreasing NF-κB, C/EBPβ and PPAR-γ in the liver and HEPG2 cells. Cobbina E et al found that the presence of steatosis, oxidative stress and inflammatory mediators like TNF-α and IL-6 has been implicated in the alterations of nuclear factors in NAFLD (47). Chen HW et al (48) and Li F et al (49) found AG inhibit IL-1, IL-6 and TNF-α-induced inflammation in vivo and in vitro disease models.…”
Section: Discussionmentioning
confidence: 99%